The Role of Grandparenting in Problematic Behaviors among Kindergarten B Children in Lamongan Regency - Nurul Maslachah; Sulhatul Habibah; Moh Vito Miftahul Munif (Universitas Sebelas Maret, 2026)
This study aims to analyze the role of grandparenting on problematic behavior in kindergarten B children in Lamongan Regency, specifically at Harapan Kindergarten in Kalitengah Village, Pancasila Kindergarten in Blajo Village, and Tunas Jaya 1 Kindergarten in Madulegi. The focus of the study was on the parenting patterns of grandparents as primary caregivers and their implications for children's emotional regulation, independence, and social behavior in the school environment. This study used a qualitative approach with a descriptive approach. The subjects were grandparents who were the primary caregivers of kindergarten B children at the three institutions. Data collection was conducted through semi-structured interviews, focusing on aspects of parenting background, parenting styles, problematic behaviors, and coping strategies. Data were analyzed through data reduction, data presentation, and conclusion drawing to identify patterns of relationships between parenting practices and children's behavior. The results showed that grandparenting practices were generally driven by economic factors and family circumstances, such as parents working outside the area or divorce. The parenting patterns applied tended to be permissive and overprotective, characterized by a lack of consistent rules and a tendency to indulge children's desires. This pattern has implications for the emergence of problematic behaviors. Thus, grandparenting influences the formation of children's behavior, particularly when parenting patterns lack boundaries and consistency that support optimal social-emotional development.